The diffusion of e-commerce in UK SMEs - Wilson, Hugh; Daniel, Elizabeth; Davies, Iain A. (Westburn Publishers, 2008)
The concept of the Internet as a cluster of related innovations, along with the staged approach to organisational learning exhibited by SMEs in other domains, suggest that e-commerce is likely to be adopted in a sequence of stages. This exploratory survey, carried out by means of a postal questionnaire with 678 respondents, uses cluster analysis to derive a grouped classification of e- commerce adoption. Four groups of organisations emerge, which we term developers, communicators, promoters and customer lifecycle managers. Through inductive analysis of these groups we are able to suggest that they represent four stages in the adoption of e-commerce. Five factors found to influence this adoption are top management support, management understanding of business benefits, presence of IT skills, availability of consultancy, and prioritisation of e-commerce. In addition to these factors, several other factors influence the value of e-commerce to the enterprise for any given adoption level, notably perceived risk and customer demand. Further research is encouraged to validate and extend the stage model: further stages are hypothesised, for example, termed supply chain managers and virtual value deliverers. Implications for practitioners include the need to include customer demand information and a risk assessment in decisions on adoption, and the importance of building in-house skills as part of the adoption plan.